2023
DOI: 10.48550/arxiv.2303.16107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scale-invariant inflation

Abstract: We examine a scalar-tensor model of gravity that is globally scale-invariant. When adapted to a spatially flat Robertson-Walker metric, the equations of motion describe a dynamical system that flows from an unstable de Sitter space to a stable one. We show that during this transition inflation can occur. Moreover, at the final fixed point, a mass scale naturally emerges that can be identified with the Planck mass. We compute the inflationary spectral indices and the tensor perturbation and we compare them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…2 The earlier works of refs. [189][190][191][192] have analytically confirmed that inflation in a scaleinvariant Universe as discussed in ref. [188] is a viable model for the origin of structure as far as inflationary observables are concerned.…”
Section: Jcap07(2024)058mentioning
confidence: 61%
See 2 more Smart Citations
“…2 The earlier works of refs. [189][190][191][192] have analytically confirmed that inflation in a scaleinvariant Universe as discussed in ref. [188] is a viable model for the origin of structure as far as inflationary observables are concerned.…”
Section: Jcap07(2024)058mentioning
confidence: 61%
“…In this picture inflation is then accompanied by a spontaneous/dynamical breaking of scale-invariance and the emergence of a mass scale not present in the original action. Subsequent works have established analytically that the spectral indices predicted by this model fall well within current experimental constraints [189][190][191], even when one-loop quantum corrections are considered [192]. Scale-invariance and inflation have also been studied in other papers.…”
Section: Jcap07(2024)058mentioning
confidence: 83%
See 1 more Smart Citation